Effects of rare-earth element yttrium (Y) on the solid-particle erosion resistance of AlCrFeNi medium-entropy alloy at ambient and elevated temperatures - Xu, Zhen; Diao, Guijiang; Tang, Yunqing; Chen, Keyang; Lin, Kaifan; He, Anqiang; Fraser, Doug; Li, Jing; Chung, Rei; Li, Q. Y.; Li, D. Y. (Frontiers in Coatings, Dyes and Interface Engineering, 2025)
High-entropy alloys (HEAs) and medium-entropy alloys (MEAs) have demonstrated many superior properties, including high strength, toughness, and thermal stability. Among MEAs, AlCrFeNi has received considerable attention due to its well-balanced mechanical properties and cost-effectiveness, making it a promising candidate for industrial applications. It is known that rare-earth elements can effectively enhance the oxidation resistance of alloys containing passive elements. In this study, AlCrFeNi MEAs with Y additions (0.5, 1.0, and 1.5 wt.%) were fabricated by arc melting. Microstructures of fabricated samples and their mechanical properties and resistance to air-jet sand erosion were investigated at both room temperature (20°C) and elevated temperature (700°C). For the sake of comparison, a commercial nickel-based Waspaloy superalloy was also evaluated. At both room and elevated temperatures, the AlCrFeNi MEA demonstrated high superiority over the widely used nickel-based superalloy. The Y additions increased the hardness and yield strength of the MEA, leading to improved erosion resistance at room temperature, which was more obvious at elevated temperatures, largely benefiting from the improved resistance to accelerated oxidation at elevated temperatures. The obtained information highlighted the beneficial effects of the minor Y additions in enhancing both the mechanical performance and high-temperature durability of the AlCrFeNi MEA, which would help extend the application of the MEA to higher temperatures.